2006
DOI: 10.1002/dvdy.20989
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Hand2 is sufficient for neurogenesis and cell type–specific gene expression in the enteric nervous system

Abstract: The basic helix-loop-helix DNA binding protein Hand2 is expressed in neural crest-derived precursors of enteric neurons and has been shown to affect both neurogenesis and neurotransmitter specification of noradrenergic sympathetic ganglion neurons. In the current study, our goal was to determine whether

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
98
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(99 citation statements)
references
References 52 publications
1
98
0
Order By: Relevance
“…were viable, healthy and fertile (Hendershot et al, 2007;Hendershot et al, 2008) and showed no alterations in skull morphology (data not shown). We next crossed Hand2 fl/fl mice with the Wnt1-Cre transgenic strain to target the Hand2 gene deletion to NCCs (Chai et al, 2000).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…were viable, healthy and fertile (Hendershot et al, 2007;Hendershot et al, 2008) and showed no alterations in skull morphology (data not shown). We next crossed Hand2 fl/fl mice with the Wnt1-Cre transgenic strain to target the Hand2 gene deletion to NCCs (Chai et al, 2000).…”
Section: Discussionmentioning
confidence: 90%
“…Conditional ablation of Hand2 in NCCs has revealed a crucial role for Hand2 in the development of sympathetic ganglion neurons (Hendershot et al, 2008;Morikawa et al, 2007), the enteric nervous system (Hendershot et al, 2007;D'Autreaux et al, 2007) and the cardiac outflow tract (Holler et al, 2010). In addition, conditional inactivation of Hand2 in the developing palatal epithelium has uncovered a role for Hand2 in palatal shelf fusion (Xiong et al, 2009).…”
Section: Ba/bamentioning
confidence: 99%
See 1 more Smart Citation
“…The function of Hand genes in the autonomic nervous system is thus not limited to noradrenergic phenotypic expression. Because Hand2 expression in postnatal day (P)19 embryonic carcinoma cells causes the expression of peripheral neural markers, such as peripherin 1, and its expression occurs before neurons arise (Morikawa et al, 2005), crest-derived precursors may require Hand2 to become neurons rather than only for the specification of their neurotransmitter-defined identity (Hendershot et al, 2007;Howard, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Hand genes are expressed in developing mouse Hendershot et al, 2007;Hollenberg et al, 1995) and chick (Wu and Howard, 2002) gut. In situ hybridization has suggested that Hand2 is expressed in the presumptive enteric nervous system (ENS) in mice (Dai et al, 2004) and chicks (Wu and Howard, 2002).…”
Section: Introductionmentioning
confidence: 99%